VALUE ORIENTED EDUCATION (VOE) IN CONTEMPORARY EDUCATIONAL SYSTEM (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
The present study was carried out on Value Oriented Education (VOE) in relation to the most critical input to a childs growth. It brings out best of the child and moves close to the achievements. Contemporary system social values, national values, ethical and aesthetic values like truth, goodness and beauty ( Satyam , Shivam, Sundaram) which are the hub of a educational system; are being eroded speedily. This is happening all over the world. Every nation is awakened to provide significant importance to Value Oriented Educational (VOE) system. Different pedagogies and methodologies are to be applied for the transmission of accumulated normative values of truth, beauty and goodness to the succeeding generation for creating a noble and healthy nation.